Murine Neonatal Oxidant Lung Injury: NRF2-Dependent Predisposition to Adulthood Respiratory Viral Infection and Protection by Maternal Antioxidant - Hye-Youn Cho; Laura Miller-DeGraff; Ligon A. Perrow; Wesley Gladwell; Vijayalakshmi Panduri; Fred B. Lih; Steven R. Kleeberger (MDPI AG, 2021)
NRF2 protects against oxidant-associated airway disorders via cytoprotective gene induction. To examine if NRF2 is an important determinant of respiratory syncytial virus (RSV) susceptibility after neonate lung injury, Nrf2-deficient (Nrf2−/−) and wild-type (Nrf2+/+) mice neonatally exposed to hyperoxia were infected with RSV. To investigate the prenatal antioxidant effect on neonatal oxidative lung injury, time-pregnant Nrf2−/− and Nrf2+/+ mice were given an oral NRF2 agonist (sulforaphane) on embryonic days 11.5-17.5, and offspring were exposed to hyperoxia. Bronchoalveolar lavage and histopathologic analyses determined lung injury. cDNA microarray analyses were performed on placenta and neonatal lungs. RSV-induced pulmonary inflammation, injury, oxidation, and virus load were heightened in hyperoxia-exposed mice, and injury was more severe in hyperoxia-susceptible Nrf2−/− mice than in Nrf2+/+ mice. Maternal sulforaphane significantly alleviated hyperoxic lung injury in both neonate genotypes with more marked attenuation of severe neutrophilia, edema, oxidation, and alveolarization arrest in Nrf2−/− mice. Prenatal sulforaphane altered different genes with similar defensive functions (e.g., inhibition of cell/perinatal death and inflammation, potentiation of angiogenesis/organ development) in both strains, indicating compensatory transcriptome changes in Nrf2−/− mice. Conclusively, oxidative injury in underdeveloped lungs NRF2-dependently predisposed RSV susceptibility. In utero sulforaphane intervention suggested NRF2-dependent and -independent pulmonary protection mechanisms against early-life oxidant injury.